2020
DOI: 10.21203/rs.3.rs-119566/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Broad respiratory testing to identify SARS-CoV-2 viral co-circulation and inform diagnostic stewardship in the COVID-19 pandemic

Abstract: Background: SARS-CoV-2 infection can present with a broad clinical differential that includes many other respiratory viruses; therefore, accurate tests are crucial to distinguish true COVID-19 cases from pathogens that do not require urgent public health interventions. Co-circulation of other respiratory viruses is largely unknown during the COVID-19 pandemic but would inform strategies to rapidly and accurately test patients with respiratory symptoms.Methods: This study retrospectively examined 298,415 respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In a recently published study conducted in Canada, Marshal et al examined respiratory specimens of 298,415 COVID‐19 symptomatic patients for 18 possible cocirculating pathogens, including four endemic coronaviruses. This study found very low rates of SARS‐COV‐2 coinfection and significantly lower rates of coinfection for SARS‐COV‐2 virus in comparison with SARS‐COV‐2‐negative specimens 27 . In the study conducted by Hazra et al, 2535 specimens were simultaneously tested for SARS‐CoV‐2 and other pathogens, including HCoV‐OC43, on symptomatic patients.…”
Section: Discussionmentioning
confidence: 78%
“…In a recently published study conducted in Canada, Marshal et al examined respiratory specimens of 298,415 COVID‐19 symptomatic patients for 18 possible cocirculating pathogens, including four endemic coronaviruses. This study found very low rates of SARS‐COV‐2 coinfection and significantly lower rates of coinfection for SARS‐COV‐2 virus in comparison with SARS‐COV‐2‐negative specimens 27 . In the study conducted by Hazra et al, 2535 specimens were simultaneously tested for SARS‐CoV‐2 and other pathogens, including HCoV‐OC43, on symptomatic patients.…”
Section: Discussionmentioning
confidence: 78%
“…The effect observed because of the intervention is suggestive of a correlation rather than direct causation, as not all variables could be controlled. The model used in this study did not adjust for viral coinfections (found to be very low, approximately 3%), 49 as well as the effect of influenza vaccination. In Alberta, influenza vaccination coverage was constant, at approximately 30% over the study period, and the annual effectiveness was largely comparable for these years.…”
Section: Discussionmentioning
confidence: 99%
“…As with other regions, ERV was the most common additional respiratory virus detected among SARS-CoV-2 positive samples, 2 which is consistent with our observations earlier in the pandemic. 4 As ERV is a common single target on multiplex respiratory assays, many studies have not been able to differentiate the two. However, published data from Australia, Austria, Canada, and the United Kingdom demonstrate rhinovirus as the predominant seasonal circulating respiratory virus since the SARS-CoV-2 pandemic started; 1,7,8 therefore, we speculate that rhinovirus is likely predominant here.…”
Section: Discussionmentioning
confidence: 99%
“…During the first three months of the pandemic in Alberta, Canada (March-May 2020), when all specimens submitted for COVID-19 testing also underwent respiratory viral multiplex testing, only 3.4% of those positive for SARS-CoV-2 were found to have a co-infecting respiratory virus. 4 The most prevalent of these respiratory viruses was either enterovirus or rhinovirus (ERV); the viral panel utilized could not distinguish these two.…”
Section: Introductionmentioning
confidence: 99%